A breathable membrane with physical holes

By adopting a three-layer structure breathable membrane design, using high-content metallocene and hydrotalcite materials, combined with the setting of through holes, the problem of separation and strength reduction caused by longitudinal holes is solved, and higher overall strength and tensile capacity are achieved. .

CN115352161BActive Publication Date: 2025-01-21SHANDONG SENBOSITE PLASTIC TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210992892.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-18
Publication Date
2025-01-21
Estimated Expiration
2042-08-18

AI Technical Summary

Technical Problem

The existing breathable membrane is prone to separation and strength reduction after the longitudinal hole is installed, resulting in tear damage.

Method used

A breathable membrane design with a three-layer structure is adopted, in which the upper and lower membranes contain high levels of metallocene, and the middle membrane contains hydrotalcite. Through holes are provided through the three-layer membrane to improve the overall strength and stability.

Benefits of technology

It effectively avoids separation and strength reduction caused by longitudinal holes, improves the overall strength and tensile capacity of the breathable membrane, and reduces the occurrence of tearing and shearing defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115352161B_ABST
    Figure CN115352161B_ABST
Patent Text Reader

Abstract

A breathable film with physical holes, comprising an upper film and a middle film that are laminated, wherein the base materials of the upper film and the middle film are high molecular organic matter; metallocene is added to the upper film and the middle film, wherein the metallocene content in the upper film is not less than 15wt%, and the metallocene content in the middle film is not less than 15wt%; and a plurality of through holes are provided, wherein the through holes pass through the upper film and the middle film, and the area of ​​the through holes does not exceed 4mm 2 The present application adopts metallocene to enhance the strength of the upper and middle membranes formed by high molecular organic matter. By setting at least two membranes, after the pores are formed, the two membranes have a certain mutual restriction effect, thereby ensuring the stability of the through holes and avoiding as much as possible the through holes from significantly reducing the strength of the breathable membrane itself.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to a breathable film with physical holes. Background Art

[0002] There are various forms of breathable membranes. Some of them are designed in the form of materials, with detachable inorganic substances attached to organic membranes, so that it looks like a whole membrane, but it is covered with various types of holes to make it breathable and water-permeable. Since this structure is set at the molecular level, the advantage is that the strength of the membrane itself can be adjusted through the ratio or preparation process to meet the requirements; the disadvantage is that since it is above the molecular level, there will be no physical holes, only micro or small holes, which also makes its air permeability and water permeability insufficient. However, when some physical holes are set in the membrane body, the following problems are prone to occur. The first is that due to the longitudinal holes, the membrane body is generally composed of multiple layers, and the longitudinal holes make it possible for the layers of the membrane body to separate; the second is that after the longitudinal holes are set, the strength of the body is reduced, especially when structural defects are formed at the edges of the longitudinal holes, which can easily cause the membrane to be torn. Damage. Summary of the invention

[0003] In order to solve the above problems, the present application proposes a breathable film with physical holes, including an upper film and a middle film that are laminated, the base materials of the upper film and the middle film are high molecular organic matter; metallocene is added to the upper film and the middle film, the metallocene content in the upper film is not less than 15wt%, and the metallocene content in the middle film is not less than 15wt%; and also includes a plurality of through holes, the through holes are set through the upper film and the middle film, and the area of ​​the through holes does not exceed 4mm 2 The present application adopts metallocene to enhance the strength of the upper and middle membranes formed by high molecular organic matter. By setting at least two membranes, after the pores are formed, the two membranes have a certain mutual restriction effect, thereby ensuring the stability of the through holes and avoiding as much as possible the through holes from significantly reducing the strength of the breathable membrane itself.

[0004] Preferably, it also includes a lower film arranged on the side of the middle film away from the upper film; the lower film contains no less than 15wt% of metallocene, and the through hole is arranged vertically through the upper film, the middle film and the lower film.

[0005] Preferably, the metallocene content in the middle film is 15wt%-25wt%, and the metallocene content in the upper film and the lower film is 25wt%-30wt%; the metallocene content in the upper film and the middle film is not less than 5wt% higher than that in the middle film, and the area of ​​the through hole is 2-4mm 2The present application sets a three-layer structure and increases the metallocene content of the upper and lower membranes, thereby improving the tensile strength of the outer membrane and forming a concave structure at the through hole to avoid deformation and tearing, thereby improving the overall strength of the breathable membrane itself.

[0006] Preferably, a light stabilizer is also added to the upper film, the middle film and the lower film; the added amount of the light stabilizer is 0.4wt%-0.8wt%; the light stabilizer is light stabilizer 944; the high molecular organic matter is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of the ethylene-vinyl acetate copolymer to polyethylene is 0-1:1.

[0007] Preferably, the through holes on the breathable membrane are evenly distributed, and the area occupied by the through holes is 0.01-0.1% of the total area of ​​the breathable membrane.

[0008] Preferably, the middle film contains hydrotalcite, and the content of the hydrotalcite is 1wt%-2wt%. In the present application, the addition of hydrotalcite to the middle film can achieve the effect of atomization, and after the hydrotalcite is added to the middle film, the product crystallizes, changes the molecular structure of the product, and also achieves the effect of improving the overall film strength. It is speculated that after the addition of hydrotalcite, the film strength of the middle film itself is weakened, but it has better bonding with the upper film and the lower film, thereby improving its integrity and improving the overall strength after the through hole is opened.

[0009] Preferably, an uppermost film of the same material as the upper film is arranged on the outer side of the upper film away from the lower film; and a lowermost film of the same material as the lower film is arranged on the outer side of the lower film away from the upper film. Each film layer of the present application is about 0.02mm. In actual use, at least two layers of film can basically meet the use requirements. After using three layers of film, due to the difference between the inside and the outside, the composition can be adjusted to achieve a better optimization effect. Using five layers of film can strengthen the structure of the outer film. The reason for using the same component reinforcement instead of thickening the thickness is mainly to avoid collateral damage as much as possible after being torn, sheared, etc., and to form a certain clamping effect between the layers.

[0010] Preferably, the synthesis is performed according to the following steps: raw materials are mixed according to the components of each layer of the breathable membrane to obtain a mixed material corresponding to each layer of the membrane;

[0011] The mixed material is fully heated and hot-melt extruded, blown, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film;

[0012] Punch holes on the raw material film to obtain a breathable membrane.

[0013] Preferably, the stirring speed during the raw material mixing is 700-1000 r / min, and the stirring time is 3-10 min.

[0014] Preferably, the holes are punched by laser or mechanical punching.

[0015] This application can bring the following beneficial effects:

[0016] 1. This application can be used to adjust the agricultural environment in the greenhouse, solve the humidity problem in the greenhouse, and achieve the effect of reducing humidity and reducing crop diseases and pests.

[0017] 2. The present application adopts metallocene to enhance the strength of the upper and middle membranes formed by high molecular organic matter. By setting at least two layers of membranes, after the pores are formed, there is a certain mutual restriction between the two layers of membranes, thereby ensuring the stability of the through holes and avoiding as much as possible the through holes from significantly reducing the strength of the breathable membrane itself.

[0018] 3. In the present application, the addition of hydrotalcite to the middle layer membrane can achieve an atomization effect. After the hydrotalcite is added to the middle layer membrane, the product crystallizes, changes the molecular structure of the product, and also achieves the effect of improving the overall membrane strength. It is speculated that after the addition of hydrotalcite, the membrane strength of the middle layer membrane itself is weakened, but it has better bonding with the upper and lower membranes, thereby improving its integrity and improving the overall strength after the through holes are opened.

[0019] 4. Each layer of the membrane of the present application is about 0.02mm. In actual use, at least two layers of membrane can basically meet the use requirements. After using three layers of membrane, due to the difference between the inside and the outside, the component adjustment can be better used to achieve a more optimized effect. The use of five layers of membrane can strengthen the structure of the outer membrane. The reason for using the same component reinforcement instead of thickness increase is mainly to avoid collateral damage as much as possible after defects such as tearing and shearing, but to form a certain clamping effect between the layers. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0021] Figure 1 This is a schematic diagram of the structure of this application.

[0022] Figure 2 It is a schematic diagram of the internal structure of the present application. DETAILED DESCRIPTION

[0023] In order to clearly illustrate the technical features of this solution, this application is elaborated in detail below through specific implementation methods.

[0024] The present application relates to a method for synthesizing a breathable membrane with physical pores. The technical solution of the present application is explained below through its specific synthesis and characterization methods.

[0025] The synthesis of raw material films is as follows:

[0026] S1. The raw materials are mixed according to the components of each layer of the breathable membrane to obtain a mixed material corresponding to each layer of the membrane; the stirring speed during the mixing of the raw materials is 700-1000r / min, and the stirring time is 3-10min;

[0027] like Figure 1-2 As shown, the upper film 1, the middle film 2 and the lower film 3, the base materials of the upper film 1, the middle film 2 and the lower film 3 are high molecular organic matter; metallocenes are added to the upper film 1, the middle film 2 and the lower film 3, the metallocene content in the middle film 2 is 15wt%-25wt%, and the metallocene content in the upper film 1 and the lower film 3 is 25wt%-30wt%.

[0028] Light stabilizer is also added to the upper film 1, the middle film 2 and the lower film 3; the added amount of the light stabilizer is 0.4wt%-0.8wt%; the light stabilizer is light stabilizer 944.

[0029] The high molecular organic matter is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 0-1:1.

[0030] The middle layer film 2 may contain hydrotalcite, and the content of the hydrotalcite is 1 wt%-2 wt%.

[0031] The middle layer film 2 may further contain a foaming masterbatch, the content of which is 4-5 wt %.

[0032] The metallocene content in the upper film 1 and the middle film 2 is higher than that in the middle film 2 by not less than 5 wt %.

[0033] An uppermost film 4 made of the same material as the upper film 1 is disposed on the outer side of the upper film 1 away from the lower film 3 ; a lowermost film 5 made of the same material as the lower film 3 is disposed on the outer side of the lower film 3 away from the upper film 1 .

[0034] S2. The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0035] On the basis of obtaining the raw material film, the through hole 6 can also be obtained by laser drilling or mechanical drilling. The area of ​​the through hole 6 is 2-4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01-0.1% of the total area of ​​the raw material film;

[0036] Combined with the synthesis method summarized above, and combined with parameter characterization, the following specific implementation plan is carried out:

[0037] Embodiment 1:

[0038] S101. Determine the components of each layer of film:

[0039] Upper film 1:

[0040] The metallocene polyethylene content is 25 wt%;

[0041] The light stabilizer 944 is 0.4 wt%;

[0042] The balance is ethylene-vinyl acetate copolymer;

[0043] Medium film 2:

[0044] The metallocene polyethylene content is 15 wt%;

[0045] The light stabilizer 944 is 0.4 wt%;

[0046] The hydrotalcite content is 1 wt%;

[0047] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.1wt%;

[0048] The balance is ethylene-vinyl acetate copolymer;

[0049] Lower film 3:

[0050] The metallocene polyethylene content is 25 wt%;

[0051] The light stabilizer 944 is 0.4 wt%;

[0052] The balance is ethylene-vinyl acetate copolymer;

[0053] S102. Mix the raw materials of each layer of film evenly:

[0054] 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2 and 1 kg of the raw material of the lower film 3 were mixed and stirred at a stirring speed of 700 r / min for 10 min;

[0055] S103. Thermoplastic compression bonding to obtain raw material film:

[0056] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0057] S104. Raw material film performance test:

[0058] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 42s.

[0059] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 11s;

[0060] S105. Raw material film punching:

[0061] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by mechanical punching. The area of ​​the through hole 6 is 2 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.1% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0062] S106. The raw material film with through hole 6 is subjected to performance testing:

[0063] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 45s.

[0064] Embodiment 2:

[0065] S201. Determine the composition of each layer of the film:

[0066] Upper film 1:

[0067] The metallocene polyethylene content is 30wt%;

[0068] Light stabilizer 944 is 0.8wt%;

[0069] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0070] Middle layer membrane 2:

[0071] The metallocene polyethylene content is 25wt%;

[0072] Light stabilizer 944 is 0.8wt%;

[0073] The hydrotalcite content is 2wt%;

[0074] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0075] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0076] Lower membrane 3:

[0077] The metallocene polyethylene content is 30wt%;

[0078] Light stabilizer 944 is 0.8wt%;

[0079] The balance is high molecular organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1.

[0080] S202. Mix the raw materials of each layer of film evenly:

[0081] 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2 and 1 kg of the raw material of the lower film 3 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0082] S203. Thermoplastic lamination to obtain a raw material film:

[0083] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0084] S204. Raw material film performance test:

[0085] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to break was 55s.

[0086] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 27s;

[0087] S205. Raw material film punching:

[0088] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0089] S206. The raw material film with through hole 6 is subjected to performance testing:

[0090] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 63s.

[0091] Embodiment 3:

[0092] S301. Determine the components of each layer of the film:

[0093] Upper film 1:

[0094] The metallocene polyethylene content is 30wt%;

[0095] Light stabilizer 944 is 0.8wt%;

[0096] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0097] Middle layer membrane 2:

[0098] The metallocene polyethylene content is 25wt%;

[0099] Light stabilizer 944 is 0.8wt%;

[0100] The content of the foaming masterbatch is 5wt%;

[0101] The hydrotalcite content is 2wt%;

[0102] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0103] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0104] Lower membrane 3:

[0105] The metallocene polyethylene content is 30wt%;

[0106] Light stabilizer 944 is 0.8wt%;

[0107] The balance is high molecular organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1.

[0108] S302. Mix the raw materials of each layer of film evenly:

[0109] 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2 and 1 kg of the raw material of the lower film 3 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0110] S303. Thermoplastic lamination to obtain a raw material film:

[0111] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0112] S304. Raw material film performance test:

[0113] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 61s.

[0114] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 39s;

[0115] S305. Raw material film punching:

[0116] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0117] S306. The raw material film with through hole 6 is subjected to performance testing:

[0118] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 49s.

[0119] Embodiment 4:

[0120] S401. Determine the composition of each layer of the film:

[0121] Upper film 1:

[0122] The metallocene polyethylene content is 30wt%;

[0123] Light stabilizer 944 is 0.8wt%;

[0124] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0125] Middle layer membrane 2:

[0126] The metallocene polyethylene content is 25wt%;

[0127] Light stabilizer 944 is 0.8wt%;

[0128] The hydrotalcite content is 2wt%;

[0129] The content of foaming masterbatch is 4wt%;

[0130] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0131] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0132] Lower membrane 3:

[0133] The metallocene polyethylene content is 30wt%;

[0134] Light stabilizer 944 is 0.8wt%;

[0135] The balance is high molecular organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1.

[0136] S402. Mix the raw materials of each layer of film evenly:

[0137] 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2 and 1 kg of the raw material of the lower film 3 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0138] S403. Thermoplastic lamination to obtain a raw material film:

[0139] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0140] S404. Raw material film performance test:

[0141] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 58s.

[0142] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 31s;

[0143] S405. Raw material film punching:

[0144] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0145] S406. The raw material film with through hole 6 is subjected to performance testing:

[0146] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw film of 1000 mm to break was 40 seconds. It can be seen that the combination of foaming and perforation has a negative impact on the strength of the film.

[0147] Embodiment 5:

[0148] S501. Determine the components of each layer of the film:

[0149] Top film 4, upper film 1:

[0150] The metallocene polyethylene content is 30wt%;

[0151] Light stabilizer 944 is 0.8wt%;

[0152] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0153] Middle layer membrane 2:

[0154] The metallocene polyethylene content is 25wt%;

[0155] Light stabilizer 944 is 0.8wt%;

[0156] The hydrotalcite content is 2wt%;

[0157] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0158] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0159] Lower film 3, bottom film 5:

[0160] The metallocene polyethylene content is 30wt%;

[0161] Light stabilizer 944 is 0.8wt%;

[0162] The balance is high molecular organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1.

[0163] S502. Mix the raw materials of each layer of film evenly:

[0164] 1 kg of the raw material of the upper film 4, 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2, 1 kg of the raw material of the lower film 3 and 1 kg of the raw material of the lower film 5 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0165] S503. Thermoplastic lamination to obtain a raw material film:

[0166] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0167] S504. Raw material film performance test:

[0168] In the first destructive test, a No. 5 fishhook was used to pierce the raw film, and a tensile force of 10N was continuously applied. The raw film of 1000mm was measured for damage, and no damage was found within 5 minutes;

[0169] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 219s;

[0170] S505. Raw material film punching:

[0171] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0172] S506. The raw material film with through hole 6 is subjected to performance testing:

[0173] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The breakage time of the raw material film of 1000 mm was measured, and it was not broken within 5 minutes.

[0174] Embodiment 6:

[0175] S601. Determine the composition of each layer of the film:

[0176] Upper film 1:

[0177] The metallocene polyethylene content is 25wt%;

[0178] Light stabilizer 944 is 0.4wt%;

[0179] The balance is ethylene-vinyl acetate copolymer;

[0180] Middle layer membrane 2:

[0181] The metallocene polyethylene content is 15wt%;

[0182] Light stabilizer 944 is 0.4wt%;

[0183] The hydrotalcite content is 1wt%;

[0184] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.1wt%;

[0185] The balance is ethylene-vinyl acetate copolymer;

[0186] S602. Mix the raw materials of each layer of film evenly:

[0187] 1 kg of the raw material of the upper film 1 and 1 kg of the raw material of the middle film 2 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0188] S603. Thermoplastic lamination to obtain a raw material film:

[0189] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0190] S604. Raw material film performance test:

[0191] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 28s.

[0192] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm to be 5s;

[0193] S605. Raw material film punching:

[0194] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by mechanical punching. The area of ​​the through hole 6 is 2 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.1% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0195] S606. The raw material film with through hole 6 is subjected to performance testing:

[0196] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 30s.

[0197] Embodiment 7:

[0198] S701. Determine the composition of each layer of the film:

[0199] Upper film 1:

[0200] The metallocene polyethylene content is 30wt%;

[0201] Light stabilizer 944 is 0.8wt%;

[0202] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0203] Middle layer membrane 2:

[0204] The metallocene polyethylene content is 25wt%;

[0205] Light stabilizer 944 is 0.8wt%;

[0206] The hydrotalcite content is 2wt%;

[0207] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0208] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0209] S702. Mix the raw materials of each layer of film evenly:

[0210] 1 kg of the raw material of the upper film 1 and 1 kg of the raw material of the middle film 2 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0211] S703. Thermoplastic lamination to obtain a raw material film:

[0212] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0213] S704. Raw material film performance test:

[0214] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 39s.

[0215] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 13s;

[0216] S705. Raw material film punching:

[0217] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0218] S706. The raw material film with through hole 6 is tested for performance:

[0219] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 45s.

[0220] Comparative Example 1:

[0221] S801. Determine the composition of each layer of the film:

[0222] Upper film 1:

[0223] The metallocene polyethylene content is 30wt%;

[0224] Light stabilizer 944 is 0.8wt%;

[0225] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0226] Middle layer membrane 2:

[0227] The metallocene polyethylene content is 30wt%;

[0228] Light stabilizer 944 is 0.8wt%;

[0229] The content of the foaming masterbatch is 5wt%;

[0230] The hydrotalcite content is 2wt%;

[0231] The content of 2,4,6-tris[bis(methoxymethyl)amino]-1,3,5-triazine is 0.3wt%;

[0232] The balance is high molecular weight organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1;

[0233] Lower membrane 3:

[0234] The metallocene polyethylene content is 30wt%;

[0235] Light stabilizer 944 is 0.8wt%;

[0236] The balance is high molecular organic matter, which is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of ethylene-vinyl acetate copolymer to polyethylene is 1:1.

[0237] S802. Mix the raw materials of each layer of film evenly:

[0238] 1 kg of the raw material of the upper film 1, 1 kg of the raw material of the middle film 2 and 1 kg of the raw material of the lower film 3 were mixed and stirred at a stirring speed of 1000 r / min for 3 min;

[0239] S803. Thermoplastic lamination to obtain raw material film:

[0240] The mixed material is fully heated and hot-melt extruded, blow-molded, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; the thickness of each layer of the film is 0.02mm, and the thickness of the raw material film is the sum of the combined thickness of each layer of the film.

[0241] S804. Raw material film performance test:

[0242] In the first destructive test, a No. 5 fishhook was used to pierce the raw material film and a tensile force of 10N was continuously applied. The time required for the 1000mm raw material film to be damaged was 37s.

[0243] The second destructive test required replacing the raw material film, then using a No. 5 fishhook to pierce the raw material film, continuously applying a tensile force of 20N, and measuring the time required for the raw material film to break at 1000mm, which was 12s;

[0244] S805. Raw material film punching:

[0245] On the basis of obtaining the raw material film, a through hole 6 can also be obtained by laser drilling. The area of ​​the through hole 6 is 4 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.01% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0246] S806. Performance test of the raw material film with through hole 6:

[0247] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the 1000mm raw film to break was 29s. In this test, it can be seen that obvious strip-shaped induced cracks are generated, and the pulling ability between them is weakened.

[0248] Comparative Example 2:

[0249] Based on Example 1, the influence of the through hole size and the area occupied is studied:

[0250] The through hole 6 is obtained by laser drilling. The area of ​​the through hole 6 is 5 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.1% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0251] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 21s.

[0252] Comparative Example 3:

[0253] Based on Example 1, the influence of the through hole size and the area occupied is studied:

[0254] The through hole 6 is obtained by laser drilling. The area of ​​the through hole 6 is 1 mm 2 The through holes 6 on the raw material film are evenly distributed, and the area occupied by the through holes 6 is 0.1% of the total area of ​​the raw material film; the through holes 6 are arranged as circular holes;

[0255] A No. 5 fishhook was placed into the through hole 6, and a pulling force of 10N was continuously applied along the center line of the through hole 6. The time required for the raw material film of 1000mm to be damaged was measured to be 25s.

[0256] From Comparative Examples 2 and 3, it can be seen that even if the opening ratio is 0.1%, whether the opening ratio is too large or too small, it has an adverse effect on its own tensile strength. It is speculated that if the opening ratio is too small, it cannot play a role in buffering tearing, while if it is too large, it will directly affect its own strength, resulting in a decrease in tear resistance.

[0257] The above are only embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included within the scope of the claims of the present application.

Claims

1. A breathable membrane with physical holes, characterized in that: The invention comprises an upper film and a middle film which are laminated together, wherein the base materials of the upper film and the middle film are high molecular organic matter; metallocene is added to the upper film and the middle film, wherein the metallocene content in the upper film is not less than 15wt%, and the metallocene content in the middle film is not less than 15wt%; and the invention also comprises a plurality of through holes which are arranged through the upper film and the middle film, wherein the area of ​​the through holes does not exceed 4 mm 2 ; It also includes a lower film arranged on the side of the middle film away from the upper film; the lower film contains no less than 15wt% of metallocene, and the through hole is arranged vertically through the upper film, the middle film and the lower film; The metallocene content in the middle film is 15wt%-25wt%, and the metallocene content in the upper film and the lower film is 25wt%-30wt%; the metallocene content in the upper film and the lower film is not less than 5wt% higher than that in the middle film; The middle layer film contains hydrotalcite, and the content of the hydrotalcite is 1wt%-2wt%.

2. A breathable membrane with physical holes according to claim 1, characterized in that: The area of ​​the through hole is 2-4 mm 2 .

3. A breathable membrane with physical holes according to claim 1, characterized in that: Light stabilizer is also added to the upper film, the middle film and the lower film; the added amount of the light stabilizer is 0.4wt%-0.8wt%; the light stabilizer is light stabilizer 944; the high molecular organic matter is a mixture of polyethylene and ethylene-vinyl acetate copolymer, and the mass ratio of the ethylene-vinyl acetate copolymer to polyethylene is 0-1:

1.

4. A breathable membrane with physical holes according to claim 1, characterized in that: The through holes on the breathable membrane are evenly arranged, and the area occupied by the through holes is 0.01-0.1% of the total area of ​​the breathable membrane.

5. The breathable membrane with physical holes according to claim 1, characterized in that: An uppermost film having the same material as the upper film is arranged on the outer side of the upper film away from the lower film; and a lowermost film having the same material as the lower film is arranged on the outer side of the lower film away from the upper film.

6. The breathable membrane with physical holes according to claim 1, characterized in that: Synthesize according to the following steps: Mixing raw materials according to the components of each layer of the breathable film to obtain a mixed material corresponding to each layer of the film; The mixed material is fully heated and hot-melt extruded, blown, cooled and shaped, and extruded and pulled to obtain a multi-layer composite film to form a raw material film; The raw material film is perforated to obtain a breathable film.

7. A breathable membrane with physical holes according to claim 6, characterized in that: The stirring speed during raw material mixing is 700-1000r / min, and the stirring time is 3-10min.

8. A breathable membrane with physical holes according to claim 7, characterized in that: The holes are punched by laser or mechanically.

Citation Information

Patent Citations

  • Composite packaging film and preparation method thereof

    CN114274630A

  • Tear-resistant base material film

    CN115122741A

  • Covering material for greenhouse

    JP2014217335A